Promotion of sludge process reduction using low-intensity ultrasonic treatment. (20th November 2021) - Gao, Jianlei; Liu, Yan; Yan, Yixin; Wan, Junfeng; Liu, Fan
Abstract: Ultrasonication lysis-cryptic growth is an efficient, green method for the source reduction of excess sludge. However, the commonly used high-intensity ultrasound (HIU) suffers from high energy consumption and poor effluent quality. We explored the feasibility of low-intensity ultrasound (LIU) for sludge yield reduction. Batch activity assays indicated that an ultrasound specific energy (Es) of 2000 kJ/kg dry sludge (DS) could increase the dehydrogenase activity of the sonicated sludge by 30%. Further testing of the ultrasonic stimulus using a sequential batch reactor (SBR) showed that LIU reduced the sludge yield rate by 21.53% when the proportion of sonicated sludge (SP) was 20%, without affecting sludge dehydrogenase activity, effluent quality and sedimentation performance. Compared with that obtained with HIU, the sludge reduction rate obtained with LIU was reduced by half, but its energy consumption efficiency (EE) was 4 times higher (0.0606 kg DS/kWh). Repeated ultrasonic experiments confirmed that dehydrogenase activity reached a maximum of 60% after the sludge was sonicated once and decreased rapidly after two or more repeated ultrasonic irradiation cycles. Therefore, LIU application to a portion of the sludge achieved a balance between sludge activity and destruction, thereby promoting sludge reduction without effluent deterioration. Highlights: ● Low-intensity ultrasound can achieve sludge reduction while ensuring good effluent quality. ● The energy consumption efficiency improved by 4 times compared to that of high-intensity ultrasound. ● A good sludge settling performance was maintained using low-intensity ultrasonic treatment. ● Repeated ultrasound damages cells to achieve cryptic growth and promote sludge reduction.